A systematic revision of herrings (Teleostei, Clupeidae, Clupeinae) from the Oligocene and early Miocene from the Eastern Paratethys and the Carpathian Basin. Issue 2 (3rd March 2020) - Kovalchuk, Oleksandr; Baykina, Evgenia; Świdnicka, Ewa; Stefaniak, Krzysztof; Nadachowski, Adam
ABSTRACT: Clupeids are one of the most diverse groups of marine fishes represented by numerous extant genera and species. The diversity of European clupeids was even greater in the past, especially during the Paleogene and early Neogene. Here we present the results of a thorough revision of numerous fish fossils assigned to the subfamily Clupeinae. They come from Oligocene and early Miocene deposits of the former Eastern Paratethys and the Carpathian Basin, and are represented by complete and fragmented skeletons. A new endemic genus—† Rupelia Baykina and Kovalchuk, gen. nov.—is established for small-sized herrings from the early Oligocene (Rupelian) of the Caucasus. It occurred only in the Eastern Paratethys and was represented by a single species—† R. rata (Daniltshenko, 1959 ). At that time, another herring inhabited the entire Paratethys. It completely fits into † Clupeonella ( Maicopiella ) sensu Menner, 1949a —a subgenus which is raised here to genus level. Based on our review, this herring was represented during the Oligocene by † Maicopiella longimana (Heckel, 1850 ) —a widespread species with numerous fossils found in deposits mostly of Rupelian and partly of Chattian age. † Rupelia rata went extinct at the beginning of the Miocene, while † Maicopiella longimana was replaced by † M. brevicauda (Menner, 1949a ) in the Eastern Paratethys and by † Sardinella sardinites (Heckel, 1850 ) in the Carpathian Basin. A detailed morphological description of all mentioned taxa is presented. The results of our study shed more light on the diversity and distribution of herrings within the central and eastern parts of the Paratethys during the Oligocene and early Miocene.